2017
DOI: 10.1103/physreva.96.043863
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric noise sensitivity of pulse trains in an excitable microlaser with delayed optical feedback

Abstract: A semiconductor micropillar laser with delayed optical feedback is considered. In the excitable regime, we show that a single optical perturbation can trigger a train of pulses that is sustained for a finite duration. The distribution of the pulse train duration exhibits an exponential behavior characteristic of a noise-induced process driven by uncorrelated white noise present in the system. The comparison of experimental observations with theoretical and numerical analysis of a minimal model yields excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…In particular, it has been suggested that this property could be used in the construction of bioinspired ‘neuromorphic’ photonic resonators that process information through light pulses alone [ 21 , 22 ]. Supporting this perspective are results that show that pulse-timing patterns due to regeneration of excitation exist in a coherently driven laser [ 23 ] and a wavelength tuneable semiconductor laser subject to optoelectronic delayed feedback [ 24 ] as well as in a driven laser subject to optoelectronic delayed feedback [ 25 ], and a micro-laser with integrated saturable absorber [ 26 ]. Given the similarities in excitability between neural and laser systems, it is pertinent to inquire as to which features of the regenerative process are common to both and which differ, noting that such dynamics have previously been observed in delay-coupled recurrent neural loops subject to continuous long-term stimulation [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been suggested that this property could be used in the construction of bioinspired ‘neuromorphic’ photonic resonators that process information through light pulses alone [ 21 , 22 ]. Supporting this perspective are results that show that pulse-timing patterns due to regeneration of excitation exist in a coherently driven laser [ 23 ] and a wavelength tuneable semiconductor laser subject to optoelectronic delayed feedback [ 24 ] as well as in a driven laser subject to optoelectronic delayed feedback [ 25 ], and a micro-laser with integrated saturable absorber [ 26 ]. Given the similarities in excitability between neural and laser systems, it is pertinent to inquire as to which features of the regenerative process are common to both and which differ, noting that such dynamics have previously been observed in delay-coupled recurrent neural loops subject to continuous long-term stimulation [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…A numerical and theoretical analysis concluded that pulse interaction (attractive and/or repulsive) should lead to asymptotic states consisting of regular spiking patterns. In the presence of noise (pump noise in particular), it was shown that the induced stochasticity in the dynamics is biased towards the erasure of spikes [33]: noise plays an asymmetric role. It is more likely to prevent the regeneration of a pulse than creating a pulse from nothing.…”
Section: Computing With Single Nodementioning
confidence: 99%
“…An example is the characterisation of a micropillar laser with an intra-cavity saturable absorber, which was shown in [24,25] to be described well by the Yamda model with σ close to one. Subsequent work in [33,34] considered sustaining pulse trains in such a device via optical feedback, where the gain decays faster than the absorption. In recent work [27], we consider a relatively short all-fibre laser, comprised of a 1 m gain section and an absorber section ranging from 0.21 m to 1.48 m, and showed that it displays Q-switching.…”
Section: Propositionmentioning
confidence: 99%